Aging steller sea lions by growth layer groups in teeth - Takeomi Isono; Yumi Kobayashi; Vladimir N. Burkanov; Orio Yamamura (Wildlife Society Bulletin)
ABSTRACT Accurate age determination of individuals is crucial in estimating age structure in populations as well as age‐specific rates of reproduction and survival. We examined growth layer groups (GLGs) in the canine, incisor, and postcanine teeth of Steller sea lions (Eumetopias jubatus) to find the optimal method to determine their age using 18 known‐age animals, from data collected in Hokkaido, Japan, 1995–2011. After checking to determine if the pulp cavity was open, nearly closed, or closed, teeth were sectioned and stained. Occlusion of the canine pulp cavity occurred at older ages than with the incisor and postcanine teeth. Initially, the number of GLGs in both dentin and cementum was compared with actual ages to confirm the age determination method. Dentin GLGs appeared clearly in all of the canines, incisors, and postcanines. The number of GLGs was consistent with the actual age, with the exception of teeth with a closed pulp cavity. With respect to cementum, appearance of GLGs was rather obscure and no GLG was detectable at ages of 0 and 1 year. Thus, the number of GLGs in cementum could be assigned as age when the value 1 year was added. We examined the accuracy and precision of the tested methods using an independent reader, who did not know the actual ages. By conducting readings 3 times, we used coefficient of variation (CV) to determine precision. The most precise CV was obtained in dentin canine (6.7%). Accuracy was calculated as proportion of estimates without error. The greatest accuracy in dentin was observed in canines (0.83, n = 18), whereas that of cementum was in postcanines (0.36, n = 11). We concluded that canine dentin provided the most precise and accurate ages for Steller sea lions. Once closure of the pulp cavity in canines has occurred at the age of 15–16 years in males and 11–12 years in females, we recommend postcanine cementum be used. © 2019 The Wildlife Society.